Predictors of ongoing attendance at an Australian publicly funded specialist obesity service - Louise Brightman; Hsin‐Chia Carol Huang; Ekavi Georgousopoulou (Obesity Science & Practice)
Abstract Introduction There is a demand for publicly funded specialist obesity services in Australia. A range of factors can impact on patient attendance which can result in poorer health outcomes. Objective To identify patient factors that predict ongoing in‐person attendance following initial medical assessment at the Canberra Obesity Management Service. Methods Data were collated from two retrospective reviews (July 2016–June 2017 and July 2018–June 2019). Predictive modeling was used to determine the likelihood of ongoing attendance. Results A total of 396 patients were identified. Mean age was 45.4 years (SD 13.1), mean weight was 139.5 kg (SD 27.8) and mean Body Mass Index was 49.87 kg/m2 (SD 8.7). Demographics and anthropometrics were not predictive of ongoing attendance. Patients with a higher comorbidity burden were more likely to continue attending (p < 0.001). Patients with obstructive sleep apnea (OSA) were 4.9 times more likely to continue attending (p < 0.001). Hypertension was more common among patients who continued attending (p = 0.005); however, this relationship was no longer significant when using a multi‐adjusted model. Comorbid depression and/or anxiety diagnoses were not predictive of ongoing attendance although the p‐value for anxiety severity classification approached significance. Conclusions Findings are consistent with existing evidence linking OSA and attendance at specialist obesity services. Hypertension was predictive of ongoing attendance and warrants further research. Determining if anxiety is a true barrier to attendance at specialist obesity services may have implications in terms of optimizing diagnosis and treatment prior to referral or in the early stages of obesity management.